(15)N Hyperpolarization of Dalfampridine at Natural Abundance for MRI - Skovpin, Ivan V. (Chemistry, 2019)
Signal Amplification by Reversible Exchange (SABRE) is a promising method for NMR signal enhancement and production of hyperpolarized molecules. As nuclear spin relaxation times of heteronuclei are usually much longer than those of protons, SABRE-based hyperpolarization of heteronuclei in molecules is highly important in the context of biomedical applications. In this work, we demonstrate that the SLIC-SABRE technique can be successfully used to hyperpolarize (15)N nuclei in dalfampridine. The high polarization level of ca. 8% achieved in this work allowed us to acquire (15)N MR images at natural abundance of the (15)N nuclei for the first time.